(3JMQjQ cJGH KGhPhSHhS aj GdCjGe hGddjGdis - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3KGhPhSjhSs
(3ChdgG (B:s
(3UOQ GdcJGH (B: (3GdTeS JJMQc MQcI eYJOdI VO MQcI Gdcd Ydi efWbI GdHQhL s
(3BNQgG (B:s
(3aEPf GdMce KGHJ hgPG BNQ eG CQOfGg s
(3ef cJGH (B34 (3MSGHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B512 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B28 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs